STUDY OF THE PRACTICE OF READING SURAH AL-ISRA VERSES 79-82 AT DUHA TIME AT HIDAYATUL ISLAMIYAH PESANTREN - Abd. Wahid; Dewi Putri Erdina; M Mahmudulhassan (Universitas Muhammadiyah Surakarta, 2022)
The early tradition of reading Surah al-Isra by the Prophet. done at night which is read in its entirety before the Prophet Saw sleep. This is different from the phenomenon that occurs at the Hidayatul Islamiyah Islamic Boarding School, where they only practice four verses from Surah al-Isra, namely verses 79-82 which are read during duha. Based on this phenomenon, the researcher examines the practice, understanding of teachers and students and the meaning of these readings. This research is a qualitative research with a field study approach. Data was collected through observation techniques, interviews and documentation. The results showed that reading Surah al-Isra verses 79-82 was carried out in congregation after the Duha prayer followed by recitation of remembrance and other prayers. The teacher's understanding of the four verses is in line with the exegetes' interpretation, but not perfect. While the students' understanding of the contents of the verse can be grouped into two, namely understanding based on the translation of the pronunciation only, and understanding of the interpretation of the verse in general. Their understanding is also in line with the interpretation of the interpreter and the understanding of the teacher. As for the meaning of the practice of reciting Surah al-Isra verses 79-82, they include giving peace and self-submission to Allah Swt, ease in studying knowledge, smooth sustenance and closeness to Allah Swt and departure in worship.